PixelCampus: A Retro-Style Exploration Game for Student Orientation at Yildiz Technical University - Ocal, Baris; Senel, Idil; Cimen, Adviye Ayca Unluer (SPRINGER INTERNATIONAL PUBLISHING AG, 2025)
Navigating a large university campus can be an overwhelming experience, particularly for first-year students. PixelCampus is a gamified campus orientation tool developed for Yildiz Technical University, designed to transform this challenge into an engaging retro-style exploration game. By integrating serious game mechanics, pixel-art aesthetics, and user-centered design, PixelCampus allows students to explore virtual recreations of real-life campus spaces, interact with non-playable characters (NPCs), and complete quests and mini-games that reinforce their understanding of key university facilities and services. The development of PixelCampus follows an iterative research-throughdesign approach, utilizing Blender-modeled environments with shader-based rendering for stylized yet spatially accurate representations of the YTU campus. The game was evaluated through a two-phase survey with 102 students, ensuring consistency in participant responses before and after prototype testing. Results indicate that gamification significantly enhances student engagement, usability, and orientation effectiveness, confirming the potential of serious games in real-world onboarding scenarios. Future iterations of PixelCampus aim to expand interactive content, accessibility features, and AI-driven user experiences, with broader applications in corporate training, museum navigation, and smart city exploration. This study highlights PixelCampus as a model for future innovations in game-based orientation systems, demonstrating how interactive media can enhance spatial awareness, engagement, and institutional integration.
Keywords: Video Games; Gamification; Orientation; Serious Games; Student Onboarding; Computer Science